An advanced mock circulation loop for in vitro cardiovascular device evaluation. Issue 6 (3rd February 2020) - Gregory, Shaun D.; Pauls, Jo P.; Wu, Eric L.; Stephens, Andrew; Steinseifer, Ulrich; Tansley, Geoff; Fraser, John F.
Abstract: Controlled and repeatable in vitro evaluation of cardiovascular devices using a mock circulation loop (MCL) is essential prior to in vivo or clinical trials. MCLs often consist of only a systemic circulation with no autoregulatory responses and limited validation. This study aimed to develop, and validate against human data, an advanced MCL with systemic, pulmonary, cerebral, and coronary circulations with autoregulatory responses. The biventricular MCL was constructed with pneumatically controlled hydraulic circulations with Starling responsive ventricles and autoregulatory cerebral and coronary circulations. Hemodynamic repeatability was assessed and complemented by validation using impedance cardiography data from 50 healthy humans. The MCL successfully simulated patient scenarios including rest, exercise, and left heart failure with and without cardiovascular device support. End‐systolic pressure‐volume relationships for respective healthy and heart failure conditions had slopes of 1.27 and 0.54 mm Hg mL −1 (left ventricle), and 0.18 and 0.10 mm Hg mL −1 (right ventricle), aligning with the literature. Coronary and cerebral autoregulation showed a strong correlation ( R 2 : .99) between theoretical and experimentally derived circuit flow. MCL repeatability was demonstrated with correlation coefficients being statistically significant ( P  < .05) for all simulated conditions while MCL hemodynamics aligned well with human data. This advanced MCL is a valuable tool for inexpensive and controlled evaluation of cardiovascular devices.